Sumber Daya Manusia (Sdm) Sebagai Tantangan Dalam Pengembangan Perbankan Syariah Di Indonesia - Andriani, Desi; Andrini, Rozi (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The 1998 financial crisis has affected the Indonesian financial sector in several ways, particularly the banking sector. The creation of an alternative sharia-based banking system that is free from usury and based on profit sharing in accordance with sharia principles, helped overcome the liquidity problems faced by many conventional banks. The lack of human resources (HR) with the necessary skills to meet business demands is a major challenge that Islamic banking must face today. The purpose of this study is to examine the importance for Islamic banks to continuously strive to upgrade the quality of their human resources to compete in the digital era and make Islamic banks more competitive in the financial sector. The research uses a desk study approach to identify the challenges and needs of HR development in Islamic banking, focusing on the aspects of technical and sharia competencies. The analysis shows that Islamic banking requires human resources with multidisciplinary skills in economics and sharia to support product innovation and sharia-compliant banking services. Targeted HR development is needed so that Islamic banks can adapt to technological advances and meet market demand for competitive and sharia-compliant financial services. Keywords: Human Resources, Challenge Islamic Banking